ANALISIS PENGARUH PRODUK, HARGA, PROMOSI, DAN SALURAN DISTRIBUSI TERHADAP PERILAKU PEMBELIAN KONSUMEN PADA PRODUK MIE INSTAN INDOMIE DI YOGYAKARTA - Purwo, Irfan Anjas; Adhilla, Fitroh (Jurnal Fokus Manajemen Bisnis, 2018)
This study aims to determine the effect of the product, price, promotion and distribution channels on the buying behavior of Indomie instant noodle consumers in the city of Yogyakarta. The dependent variable used is Purchasing Behavior, while the independent variables are Product, Price, Promotion and Distribution Channels. The population in this study is the people of the city of Yogyakarta, aged 18 years and over and have bought Indomie instant noodles which were then taken as many as 95 samples. The instrument test used was Confirmatory Factor Analysis (CFA) with a confidence level of 5% and hypothesis testing was performed using the t test and F test. The results of this study showed that the product had a positive and significant effect on purchasing behavior not proven with a probability value of 0.208 greater than Î± 0.05. Price has a positive and significant effect on buying behavior is not proven with a probability value of 0.147 greater than Î± 0.05. Promotion positive and significant effect on purchasing behavior is proven, with a probability value of 0.002 smaller than Î± 0.05 and the distribution channel has a positive and significant effect on purchasing behavior not proven, with a probability value of 0.186 greater than Î± 0.05. While simultaneously the independent variable has a significant effect on Purchasing Behavior, with a significance value of 0.000 less than Î± 0.05. The coefficient of determination is 0.381 which means that all independent variables of 38.1% can explain the dependent variable of buying behavior while the remaining 61.9% is influenced by other factors.